Transcriptional engineering for improved microbial cell performances in biofuel production - Geng, Hefang (2016)
Escherichia coli and Saccharomyces cerevisiae are widely used to produce different kinds of compounds because they have several advantages over other organisms, such as short growing period, well-known genetics and metabolism, and availability of genetic manipulation tools. Biofuels have attracted researchers’ attention as they are cleaner and more sustainable compared with fossil fuels. When using Escherichia coli or Saccharomyces cerevisiae for biofuel production, one major challenge is that biofuels are highly toxic to them. Various strain engineering methods have been applied to improve microbes’ performances under stress conditions. Transcriptional engineering can be used as an alternative strain engineering method, as it is less time-consuming and labor-intensive than classical strain engineering, and does not require comprehensive genetic and metabolic information as compared with rational metabolic engineering approach. In this study, transcriptional engineering of cAMP receptor protein (CRP) and transcription factor IIB (TFIIB) was employed to improve E. coli strain tolerance towards isobutanol and S. cerevisiae strain oxidative stress resistance, respectively. The mechanism and applications of CRP engineering to elicit improved cell performances were also discussed. For transcriptional engineering, error-prone PCR and saturation mutagenesis were used to introduce mutations into CRP or TFIIB. The constructed random mutagenesis libraries were then subcultured in medium supplemented with certain stressors. After 3-5 rounds of enrichment, strains with improved traits were isolated and their growth were verified. Other characteristics of the obtained mutants were also investigated, such as their cross-tolerance towards other stresses, transcription profiles and intracellular reactive oxygen species level. Specifically, the isobutanol tolerant IB2 of E. coli had improved growth rates (0.18 h-1) than the control (0.05 h-1) in the presence of 1.2% isobutanol. When challenged with 1% isobutanol, IB2 had as many as 308 genes with altered expression level, with the major functional groups of genes related to acid resistance, nitrate reduction, flagella and fimbrial activity, and sulfate reduction and transportation. The oxidative stress resistant M1 (A330S) of S. cerevisiae had significantly increased growth rate (0.423 h-1) than the control (completely inhibited) under 8mM H2O2 stress. M1 also had cross-tolerance towards 1.5M NaCl, higher survival rate under 10mM H2O2, and higher catalase activity than the control, but the final ethanol production didn’t show any improvement.